Saṅgharakkhitamahāsāmi Therʻ ʼA rhaṅʻ cī raṅʻ toʻ mū ʼapʻ so "Vuttodaya chanʻʺ kyamʻʺ", nhaṅʻʹ ta kva l*ṅʻʺ e* ʼa bhvaṅʻʹ phracʻ kunʻ so Vacanatthajotikā ṭīkā, Chappaccayadīpaka, Sududdasavikāsinī sa ññī proṅʻ lyhamʻʺ chanʻʺ ṭīkā 3 kyamʻʺ tuiʹ kui ta poṅʻʺ taññʻʺ cī cañʻ puṃ nhipʻ ʼapʻ so Chanʻʺ ṭīkā suṃʺ coṅʻ tvai pāṭhʻ - Saṅgharakkhita, 13th cent (Jambūʹ Mitʻ chve Piṭakatʻ Puṃ nhipʻ tuikʻ, 1938)
Sangharakkhita's Vuttodaya, medieval verse work on Pali metrics and rhythmics (versification) and commentaries, Vepullabuddhis's Vacanatthajotikā ṭīkā, Paññāsīhamahāsaddhamma's Chappaccayadīpaka, and Sududdasavikāsini.